Universal Borromean Binding in Spin-Orbit-Coupled Ultracold Fermi Gases - Xiaoling Cui; Wei Yi (Physical Review X, 2014)
Borromean rings and Borromean binding, a class of intriguing phenomena as three objects are linked (bound) together while any two of them are unlinked (unbound), widely exist in nature and have been found in systems of biology, chemistry, and physics. Previous studies have suggested that the occurrence of such a binding in physical systems typically relies on the microscopic details of pairwise interaction potentials at short range and is, therefore, nonuniversal. Here, we report a new type of Borromean binding in ultracold Fermi gases with Rashba spin-orbit coupling, which is universal against short-range interaction details, with its binding energy only dependent on the s-wave scattering length and the spin-orbit-coupling strength. We show that the occurrence of this universal Borromean binding is facilitated by the symmetry of the single-particle dispersion under spin-orbit coupling and is, therefore, symmetry selective rather than interaction selective. The state is robust over a wide range of mass ratios between composing fermions, which are accessible by Li-Li, K-K, and K-Li mixtures in cold-atom experiments. Our results reveal the importance of single- particle spectral symmetry in few-body physics and shed light on the emergence of new quantum phases in a many-body system with exotic few-body correlations.